"Every Citizen is Harsh to Foreigners": Rousseau and the Problem of Nationalism. (2nd January 2020) - King, Joshua D.
Abstract: Rousseau acknowledges that citizenship renders individuals hostile to those outside their own state. In Emile he seems to minimize this problem, saying that the important thing is to be good to those with whom one lives. In the Social Contract, however, Rousseau designs a state that does not adopt this cavalier disposition toward the problem of nationalism. I argue that Rousseau addresses citizens' tendency toward nationalism by cultivating the sentiments in ways that generate a sense of compassion for those outside one's own state. Rousseau builds national institutions modeled after the sentiments of pity and self-preservation to promote a humane view of outsiders and to limit the uses of war.